Analisis Perubahan Lahan Di Kecamatan Parongpong Menggunakan Citra Satelit Sentinel.2 - Akhmad E Firlli Dimyati; Lili Somantri; Nanin Trianawati S (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2022)
Parongpong sub-district is a suburban area where this area is one of the favorite areas in selecting residential areas, on the other hand, this area is still dominated by agricultural land. The importance of monitoring land change in an area, especially in suburban areas is very important. The use of medium-resolution satellite imagery data would be a good choice because of the easy access and availability of free data. Sentinel-2 is one of the free medium resolution satellite imagery which has a spatial resolution of 10 meters in the visible channel. The method used is remote sensing with the OBIA (Object-Based Image Analysis) approach with temporal data for two years from 2017-to 2019. The image accuracy test resulted in an Overal Accuracy value of 94.8% and a Kappa Accuracy value of 95.04%. The results of the study show that the rate of land-use change that occurred in the Parongpong Subdistrict over a period of two years, starting in 2017 to 2019, has a rate of change in the value range between -0.21% to 0.17%. The largest reduction in land use was in scrub and empty land by -8.9 Ha and the largest increase in land use for Settlements and Activities by 7.27 Ha. . Patterns of change that occur are only in four types of forest land use, bush scrub, where the pattern of change that occurs is the use of forest land to settlement and fields. Meanwhile, shrubs become fields and settlements